Strategi Promosi Melalui Pemanfaatan Media Sosial Instagram Dalam Meningkatkan Penjualan pada Home Industry Baso Aci Mahira Lamongan - Latif Syaipudin; Idah Awwalin (Eastasouth Institute, 2022)
The background of this research is that social media can be used as a marketing strategy to make it more targeted. This can be used as a vehicle to market the product. The purpose of this research is to describe the planning, implementation and supervision, obstacles and solutions that are carried out through social media Instagram in increasing sales at the home industry Baso Aci Mahira Lamongan. The method in this study uses a qualitative approach with a descriptive type. The results in this study are: 1) The planning, implementation and supervision are used as a communication tool to carry out marketing. 2) The obstacle that occurs is the increasing number of business competitors, the solution is to promote with social media.